Identity among Turkish Shi'is: An Ethnographic Study - Sevgi, Mehmet Ali (Religions, 2023)
This article examines the cultural identity of Turkish Shi’is in a border province in East Turkey and how their ethnic and religious identities are positioned within the political and cultural context of Turkey. Shi’is living in Igdir, the easternmost province of Turkey, may share the ethnicity of the majority in Turkey, but they are in the minority in terms of their religious identity. Their cultural identity is shifting contextually and is always under construction. In this context, cultural theorist Stuart Hall explains identity as a never-ending construction, a process never completed—always in progress. This paper traces the multilayered and interdisciplinary approach of Hall’s identity interpretations and applies them to discuss the social, cultural, and political positionings of Igdir Ja’faris in Turkey. The study uses ethnographic data based on field observation and semi-structured interviews with Turkish Ja’faris in Igdir.